Best Answer

It is an algabraic expession without knowing whether or not 2b and 3a are plus or minus

Q: What is -6a 2b 3a-4b-5a?

Write your answer...

Submit

Still have questions?

Continue Learning about Calculus

4y - 4 + 3s + 7 - 6a - 4 = 0 4y + 3s + 7 - 6a - 4 = 4 4y + 3s - 6a - 4 = 4 -7 4y + 3s -6a = 4 - 7 + 4 4y + 3s - 6a = -3 + 4 4y + 3s - 6a = 1 y + 3s - 6a = 1/4 y = -3s + 6a + 1/4 3s = -y + 6a + 1/4 s = -1/3y + 6a + 1/4 -6a = -1/3y + a + 1/4 -a = -1/3y x 1/6 + a + 1/4 x 1/6 a = 1/18y - 1 - 1/24 a = 1/18y - 25/24

ganesh

(2a^2b^2)^3(-7a^13b^2)

a^2b^2c^2 ^2 is squared

2 [x - B] = 5B + 3Perform the indicated multiplication on the left side:2x - 2B = 5B + 3Add 2B to each side of the equation:2x = 7B + 3Divide each side by 2 :x = 7/2 B + 3/2

Related questions

2a+2b+3a+3b+a+b= 6a+6b 2a+3a+a=6a 2b+3b+b=6b

7(a-2b)-6(a-4b) 7a - 14b - 6a - 24b 7a - 6a - 14b - 24b a - 38b

6a -12b + 30 = 6 (a - 2b + 5)

4(2a+b) + 2(6a+2b) Working this out it is: 8a + 4b + 12a + 4b = 20a + 8b or 4(5a+2b).

10a - 10 b

7(a-2b)-6(a-4b) 7a - 14b - 6a - 24b 7a - 6a - 14b - 24b a - 38b

6 is the average of 2a and a - 2b so 12 = 2a + a - 2b = 3a - 2b3 is the average of 2a - b and 4a + 3b so 6 = 2a - b + 4a + 3b = 6a + 2bAdding the two equations gives: 18 = 9a so that a = 2Substituting for a in the first gives 12 = 6 - 2b so that b = -36 is the average of 2a and a - 2b so 12 = 2a + a - 2b = 3a - 2b3 is the average of 2a - b and 4a + 3b so 6 = 2a - b + 4a + 3b = 6a + 2bAdding the two equations gives: 18 = 9a so that a = 2Substituting for a in the first gives 12 = 6 - 2b so that b = -36 is the average of 2a and a - 2b so 12 = 2a + a - 2b = 3a - 2b3 is the average of 2a - b and 4a + 3b so 6 = 2a - b + 4a + 3b = 6a + 2bAdding the two equations gives: 18 = 9a so that a = 2Substituting for a in the first gives 12 = 6 - 2b so that b = -36 is the average of 2a and a - 2b so 12 = 2a + a - 2b = 3a - 2b3 is the average of 2a - b and 4a + 3b so 6 = 2a - b + 4a + 3b = 6a + 2bAdding the two equations gives: 18 = 9a so that a = 2Substituting for a in the first gives 12 = 6 - 2b so that b = -3

Assuming that non-leading numbers are exponents, the expression becomes12a^2b + 8a - 5a^2b + 2ab - 4ab^2 + 6ab - 2a - 3ab= 7a^2b + 6a + 5ab - 4ab^2= a*(7ab + 6 + 5b - 4b^2)

6a2

50 Like this: 30 = 2a+2b b=2a 30=6a a=5, b=10.

Divide by 6a: 6a(a + 3b)

36a2 - 60a + 25 = 36a2 - 30a - 30a + 25 = 6a(6a - 5) - 5(6a - 5) = (6a - 5)(6a - 5) = (6a - 5)2